2008
DOI: 10.1007/s10327-008-0135-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variation and molecular characterization of Fusarium species isolated from wilted Welsh onion in Japan

Abstract: Thirty-two isolates of Fusarium species were obtained from wilted Welsh onion (Allium fistulosum) grown on nine farms from six regions in Japan and identified as F. oxysporum (18 isolates), F. verticillioides (7 isolates), and F. solani (7 isolates). The pathogenicity of 32 isolates was tested on five commercial cultivars of Welsh onion and two cultivars of bulb onion in a seedling assay in a greenhouse. The Fusarium isolates varied in the degree of disease severity on the cultivars. Five F. oxysporum isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 17 publications
(14 reference statements)
3
36
0
Order By: Relevance
“…These isomers were found to be produced by A. awamori in a previous study . Previously another fumonisin producing fungus, Fusarium proliferatum has also been found to be able to infect onion bulbs (Dissanayake et al 2009a(Dissanayake et al , 2009bDu Toit et al 2003;Galvan et al 2008;Stankovic et al 2007). However, this species was not identified in any of the onion samples examined in this study (data not shown).…”
Section: Fumonisin Contamination Of Onion Samplesmentioning
confidence: 99%
“…These isomers were found to be produced by A. awamori in a previous study . Previously another fumonisin producing fungus, Fusarium proliferatum has also been found to be able to infect onion bulbs (Dissanayake et al 2009a(Dissanayake et al , 2009bDu Toit et al 2003;Galvan et al 2008;Stankovic et al 2007). However, this species was not identified in any of the onion samples examined in this study (data not shown).…”
Section: Fumonisin Contamination Of Onion Samplesmentioning
confidence: 99%
“…Traditionally, they also play a very essential role in the daily diet in many Asia countries, and many used to flavor foods. The green onions (Allium fistulosum L.), also referred to as the Welsh onion, and garlic (Allium sativum L.) belong to the family Alliaceae, which are very economically important vegetables in most East Asian countries [1][2][3]. The Allium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant and antimicrobial effects of Allium plants have been reported for times [1,4,5,10]; however, a study on the top-quality green onions and garlic produced in Taiwan is still scarce. In this study, different types of tissue of Taiwan Sun-Shin green onion and garlic were extracted from roots, stems and leaves using ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…However, RAPD analysis did not reveal a relationship between genetic and pathogenic variability of Turkish isolates. Similarly, Dissanayake et al (2009) separated F. oxysporum isolates obtained from Welsh onion into two genetic groups with 61.6% similarity, but not detected clear-cut relationship between clustering in the PCR-RFLP dendrogram and pathogenicity test. These results were in agreement with the previous studies which fail to provide a relationship between RAPD data and pathogenic groups of Fusarium oxysporum (Hernandez et al 1999;Freeman & Maymon 2000;Cramer et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Different methods have been used to assess genetic variation within populations of F. oxysporum f. sp. cepae such as Vegetative Compatibility Grouping (VCGs), Amplified Fragment Length Polymorphisms (AFLPs), Restriction Fragment Length Polymorphism (RFLP) analysis of Internal Transcribed Spacer (ITS) and Intergenic Spacer (IGS) regions of rDNA (Swift et al 2002, Galván et al 2008Dissanayake et al 2009, Bayraktar et al 2010. These studies have revealed that F. oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%